The Economic and Environmental Payoff of Green Roofs and Vertical Forests in Urban Air Pollution Mitigation - Aljehani, Abdulaziz; J. Isaifan, Rima (Urban Planning and Construction, 2025)
This study critically reviews the economic, environmental, and health impacts of integrating green infrastructure, specifically vertical forests and green roofs, into urban environments as a strategy for air pollution mitigation. A systematic review of recent studies, selected through PRISMA guidelines from Google Scholar, ScienceDirect, Springer Nature, and Cambridge University Press, was conducted. Evidence shows that green infrastructure reduces concentrations of pollutants such as PM₂.₅, NOₓ, SO₂, and O₃ through natural deposition, airflow modification, and vegetation filtering. These reductions translate into measurable health benefits, including lower rates of respiratory and cardiovascular diseases, decreased healthcare costs, and enhanced well-being. Economically, while installation costs vary by region, from $15–540 per m², long-term returns include reduced energy use from improved insulation, higher property values, and healthcare savings. However, valuation models often underestimate long-term benefits by excluding indirect savings. Policy gaps, inconsistent urban planning support, and limited economic justification remain barriers to adoption. The review highlights the need for interdisciplinary evaluation frameworks, integration of health-based urban indicators, and targeted incentives to advance implementation. Future research should prioritize region-specific, longitudinal studies to provide stronger evidence for planning decisions. Overall, green infrastructure represents a cost-effective pathway toward sustainable urban development with co-benefits for public health and the economy.